More years of education lead to more work-related training - Marcus Tamm (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
New findings show that the principle 'learning begets learning' does not only apply to early childhood education but also to the duration of schooling. - An active participation in work-related training supports career development and reduces the risk of job loss. A pioneering RWI study demonstrates that the duration of schooling and vocational education has a causal impact on how an employee acquires training throughout adulthood. Consequently, public investments in school and college education may have a significant impact on lifelong learning.
Keywords: 330